'The BRCA Clock is Ticking!': Negotiating medical concerns and reproductive goals in preimplantation genetic diagnosis. (September 2014) - Rubin, Lisa R.; Werner-Lin, Allison; Sagi, Michal; Cholst, Ina; Stern, Rikki; Lilienthal, Debra; Hurley, Karen
Abstract Despite research on BRCA1/2 mutation carriers attitudes towards preimplantation genetic diagnosis (PGD), considerably less is known about individuals' experience with its use. Through case reports of BRCA1/2 mutation carriers' thoughts on, and use of, PGD, this paper highlights how the option of PGD is experienced and negotiated in the context of reproductive and life-course goals. Drawing on qualitative interviews with 38 BRCA1/2 mutation carriers, this article focuses on a subsample of 10 interviewees who sought consultation for, and/or attempted, PGD, with in-depth reports of 3 cases and summary decisions of the remaining 7. Three couples decided against PGD, and one was deciding at the time of the interview. Interviewees discuss key aspects of their experience prior to, and going through, PGD for BRCA1/2, including potential challenges of becoming pregnant through PGD and of heightened pressure to achieve their reproductive goals more quickly. Despite considerable focus on ethical issues in screening embryos for mutations associated with adult-onset cancer risk, less attention has been paid to the technical, logistical, and related psychosocial issues. Narrative case reports may help individuals develop appropriate expectations of PGD for BRCA prepare for possibly challenging decisions and outcomes, and ultimately determine whether it is compatible with their reproductive goals.